Completeness of Facilities and Infrastructure at Swadaya Kendal Special School (SLB) - Ika Asmani Nanda Setya Husada (International Journal of Science and Society, 2023)
The availability of facilities and infrastructure in the field of education is quite important. The existence of facilities and infrastructure, especially for Special Schools (SLB), can determine whether or not the teaching and learning process runs smoothly at the school. The aim of the research carried out was to find out and explain the completeness of the facilities and infrastructure at SLB Swadaya Kendal based on the Department of Disability, as well as to find out and explain the completeness of the supporting facilities and infrastructure at SLB Swadaya Kendal based on standard facilities and infrastructure. The research was conducted using a qualitative descriptive approach. Data sources were obtained through observation, documentation, and questionnaires. The data obtained through questionnaires is the main reference in the research. Then, the data obtained through observation and documentation is used as a tool to confirm the results of the questionnaire data. The results of research regarding the completeness of facilities and infrastructure at the Kendal Swadaya Special School found that the facilities and infrastructure in the general learning room could be said to be quite complete, but unfortunately, the facilities and infrastructure in the special learning room for the disabled major were very incomplete. Then the facilities and infrastructure in the supporting space are incomplete. This then results in the facilities and infrastructure in general learning rooms, special learning rooms, and supporting rooms not being up to standard.